The Influence of Product Innovation, Product Quality, Promotion, and Price on Customer Satisfaction in Tempe Crisps Small And Medium Enterprises in Kampung Tempe Sanan, Malang City - Andreas Abeng; Cakti Indra Gunawan; Fendiyatmi Kusufa (International Research & Development for Human Beings (IRDH), 2026)
This research aims to analyze the effects of product innovation, product quality, promotion, and price on customer satisfaction of tempe chips MSMEs in Kampung Tempe Sanan, Malang City. The study employed a quantitative approach using a survey method on 96 respondents selected through purposive and incidental sampling techniques. The instrument used was a closed questionnaire with a Likert scale. Data analysis was conducted through validity tests, reliability tests, and multiple linear regression using SPSS. The results show that simultaneously, all independent variables significantly affect customer satisfaction. Partially, product quality and price have a dominant influence. In conclusion, improving product quality and implementing appropriate pricing strategies are important factors in enhancing customer satisfaction and loyalty among tempe chips MSMEs.